Nursing professionals’ knowledge in the management of newborns with neonatal abstinence syndrome - Laís Lima Silva; Juliana Guisardi Pereira (Revista Enfermagem Digital Cuidado e Promoção da Saúde)
OBJECTIVE: To identify the knowledge of nursing professionals about drug use in pregnant and postpartum women and the management of newborns with neonatal abstinence syndrome. METHOD: Quantitative, cross-sectional and descriptive field research, composed of 60 nursing professionals from the Joint Nursing Unit, Neonatal Intensive Care Unit, and Pediatric Intensive Care Unit, from August to October 2022. Structured form with sociodemographic, occupational and knowledge data about neonatal abstinence syndrome was used. Data were analyzed using descriptive statistics and chi-square test (x²), with a significance level of p<0.05. RESULTS: Knowledge deficits were observed among the participants, especially signs and symptoms of the newborn in neonatal abstinence syndrome, nursing care, and guidelines for breastfeeding. The three professional categories showed similar hit rates. CONCLUSION: There are gaps in the knowledge of nursing professionals. Therefore, there is a need for the formulation of an institutional protocol and training on the subject.